Frame Overlapping in Moral Markets: The Case of an ‘Open, Free, and Neutral’ Telecommunications Network - Arenas, Daniel; Rodón, Joan; Yter, Mireia (Journal of Management Studies, 2026)
Abstract This study explores how social movement activists, engaged in constructing and expanding moral markets, sustain the integrity of their initial moral values, avoiding dilution or cooptation by conventional market practices. Through a qualitative case study of a telecommunications network, we show that activists can expand a moral market by a process of frame overlapping, which involves the mechanisms of frame amplification with plural moral values, frame bridging with a resonant economic frame and frame extension adapting cultural templates. This process stands in contrast to previously identified dynamics in moral markets literature, such as ‘mutual cooptation’ between movements and firms, de‐coupling and re‐coupling the initial values, and ‘frame divergence’. We also underline different contextual factors that shape frame overlapping. Finally, the article examines the nature of moral markets and proposes a dynamic view of what makes a moral market ‘moral’.